Seismotomography of the mantle under the East European platform: mantle velocity boundaries - T. A. Tsvetkova; I. V. Bugaenko (Геофизический журнал, 2012)
Mantle velocity boundaries of EEP have been specified. For the upper mantle and its tranzi-tion zone dynamics of propagation of mantle velocity limits with depth has been presented. Mantle border area of EEP has been separated and corresponding high velocity inclined layers.